Morphological changes of adrenal cortex and medulla during the first 24 hours after acute hemorrhage - Yu V Yunyashina; A A Chekushkin; S A Mozerov; A N Myalin (RUDN Journal of Medicine, 2014)
Experimentally established that during the first day after acute blood loss expressed morphological changes occur in the adrenal cortex and medulla, indicating a high functional stress of the organ.